Students’ and Teachers’ Perceptions and Perspectives on Homework - Pandey, Shiv Ram; Kaudal, Durga Nidhi (Studies in ELT and Applied Linguistics, 2025)
This study uncovers perceptions and perspectives of teachers and students on homework from grade eight. The main objectives were to explore teachers’ and students’ perception on homework. It follows qualitative research method to gather and analyze data. We have reviewed some related articles on homework. To conduct this study, we have used primary as well as secondary sources of data. The major findings of this study are although some of the students who are weak, lazy and low performing feel homework as a load, however, they did not deny the fact that homework leads to invention. They were found to be doing homework. When the given homework is creative and rewarding, it can be taken as a notion of creativity for students. The study found that homework always benefits both students and teachers for improved learning, remembering, reading, and writing habits. It increases knowledge, skill and values on the part of students. Homework is essential to get involved in learning. It is an exercise to excavate creativity and critical thinking in learning, An evaluation of homework provides teachers a feedback to take right action for effective teaching and learning. Despite some issues such as burden, stress and anxiety on homework, the study concludes that giving homework to the students is always good, rewarding and meaningful. Homework supports to the students to take part in competitive tests and examination. Moreover, taking feedback can be a good source of information to design better assignment to the students from the side of teachers.